2016
DOI: 10.1016/j.plgene.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of chlorogenic acid biosynthesis in carrot root slices exposed to UV-B light

Abstract: Orange carrots are well known for their nutritional value as producers of ß-carotene, a vitamin A precursor. Lesser known, is their ability to accumulate antioxidants such as chlorogenic acid. Chlorogenic acid is produced through the same biosynthetic pathway that produces lignins, anthocyanins, flavonols and isoflavonoids, the phenylpropanoid pathway. This pathway can be induced by UV-B light and wounding to produce large amounts of chlorogenic acid. We identified a number of the carrot structural genes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 75 publications
0
22
1
Order By: Relevance
“…These genes may be key genes whose proteins catalyze CGA biosynthesis in E. ulmoides . In addition, some transcription factors (TFs) have also been reported to regulate CGA biosynthesis, including the MYB , ZIP , and WRKY families 61 64 . We identified 1,406 TF-encoding genes in E. ulmoides , representing 5.41% of the total genes.…”
Section: Resultsmentioning
confidence: 99%
“…These genes may be key genes whose proteins catalyze CGA biosynthesis in E. ulmoides . In addition, some transcription factors (TFs) have also been reported to regulate CGA biosynthesis, including the MYB , ZIP , and WRKY families 61 64 . We identified 1,406 TF-encoding genes in E. ulmoides , representing 5.41% of the total genes.…”
Section: Resultsmentioning
confidence: 99%
“…2a-c). Although a few genes involved in CGA biosynthesis had been reported in other plant species [14,[22][23][24][25][26][27][28][29][30], the molecular mechanisms underlying in leafy sweet potato remains largely unknown. In the present study, a total of 29834 genes were identi ed based on the reference guided transcriptome analysis of two genotypes at two stages.…”
Section: Discussionmentioning
confidence: 99%
“…2a-c). Although a few genes involved in CGA biosynthesis had been reported in other plant species [14,[22][23][24][25][26][27][28][29][30], the molecular mechanisms underlying in leafy sweet potato remains largely unknown. In the present study, a total of 29834 genes were identified based on the reference guided transcriptome analysis of two genotypes at two stages.…”
Section: Discussionmentioning
confidence: 99%
“…Some TFs were also reported to regulate the biosynthesis of CGA. MYB1 was an important transcriptional activator of C4H (PAL1),, while MYB 3 and 5 were found to act on the promotor of PAL3 in carrots [28]. ZIP8 could be specifically bound to the G-box element of PAL2 5'-UTR in Lonicera japonica, its overexpressing leading to a decrease in CGA content [26].…”
Section: Introductionmentioning
confidence: 99%